2022
DOI: 10.3847/1538-4357/ac86d8
|View full text |Cite
|
Sign up to set email alerts
|

Wide-band Timing of GMRT-discovered Millisecond Pulsars

Abstract: Modeling of frequency-dependent effects, contributed by the turbulence in the free electron density of interstellar plasma, is required to enable the detection of the expected imprints from the stochastic gravitational-wave (GW) background in pulsar timing data. In this work, we present an investigation of temporal variations of interstellar medium for a set of millisecond pulsars (MSPs) with the upgraded Giant Metrewave Radio Telescope (GMRT) aided by large fractional bandwidth at lower observing frequencies.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Apart from showing the aforementioned consistency between results obtained with wideand narrowband methods, Nobleson et al (2022) also emphasize an increased precision of low-frequency DM measurements and prove wide-band timing methods to be beneficial even for small fractional bandwidths. Other examples of implementations of methods presented by Pennucci et al (2014) can be found in Fonseca et al (2021) and Sharma et al (2022), where the analyses focus on detailed binary parameter estimation and study of new PTA-candidate pulsars, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from showing the aforementioned consistency between results obtained with wideand narrowband methods, Nobleson et al (2022) also emphasize an increased precision of low-frequency DM measurements and prove wide-band timing methods to be beneficial even for small fractional bandwidths. Other examples of implementations of methods presented by Pennucci et al (2014) can be found in Fonseca et al (2021) and Sharma et al (2022), where the analyses focus on detailed binary parameter estimation and study of new PTA-candidate pulsars, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Phase-coherent timing has been obtained for the GSB observations for these four MSPs and was reported in Bhattacharyya et al (2019) and Bhattacharyya et al (2022). Sharma et al (2022) reported the phase-coherent timing with GWB observations for the same MSPs, which accounts for 2− 4 yr of observational timing baseline.…”
Section: Introductionmentioning
confidence: 68%
“…The results from the timing studies will be reported in the future GHRSS publications. Sharma et al (2022) recently reported the long-term wideband timing of four GMRT-discovered MSPs. Considering band 3 detection S/N, those four MSPs are roughly 4 times weaker than the two MSPs reported in this paper.…”
Section: Discussionmentioning
confidence: 95%
“…This 2D template is created in PulsePortraiture using principal-component-decomposition (Pennucci 2019). To extract the wide-band ToA and DM from the observational data, we used the same strategy described in Sharma et al (2022).…”
Section: Toa and Dm Precisionmentioning
confidence: 99%
See 1 more Smart Citation